The Identification and Cytotoxic Evaluation of Nutmeg (Myristica fragrans Houtt.) and Its Substituents - Suthiwat Khamnuan; Ampai Phrutivorapongkul; Pornsiri Pitchakarn; Pensiri Buacheen; Jirarat Karinchai; Chuda Chittasupho; Mingkwan Na Takuathung; Tinnakorn Theansungnoen; Kannika Thongkhao; Aekkhaluck Intharuksa (Foods, 2023)
The aril and seed of nutmeg, Myristica fragrans Houtt. (Myristicaceae), hold significant value in various industries globally. Our preliminary research found two morphological variations: a globose shape and an oval shape. Due to these different characteristics, the safety of consumers is of primary concern. Thus, authentication and comparative pharmacological and toxicity analyses are necessary. In this study, pharmacognostic and advanced phytochemical analyses, DNA barcoding, cytotoxicity, and the anti-nitric oxide production of commercial Thai nutmeg were examined. Via morphologic examinations and TLC fingerprinting, all the sampled aril and seed were categorized into globose and oval-shaped groups. The results of HPLC, GC-MS, and LC-MS/MS experiments revealed distinct differences between these groups. The DNA barcoding of the trnH-psbA region using the BLAST method and neighbor-joining tree analyses confirmed the globose nutmeg as M. fragrans and the oval-shaped variant as M. argentea. A comparison was then carried out between the potential toxicity and anti-inflammatory capabilities of M. fragrans and M. argentea. Cytotoxicity tests on HaCaT, 3T3-L1, Caco-2, HEK293, and RAW264.7 were performed using both methanolic extracts and volatile oil from the arils and seeds of both species. This study concludes that blending or substituting these two species maintains their therapeutic integrity without posing safety concerns.